Analisis Hambatan dan Solusi Perlindungan Hukum Konsumen dalam Jual Beli Tas Branded Via Tiktok Shop - Adinda Putriani; Hendro Saptono; Rinitami Njatrijani (Faculty of Law, Diponegoro University, 2023)
Online buying and selling is carried out by consumers to facilitate the acquisition of goods, but there are obstacles in providing legal protection to consumers. This research analyzes legal protection barriers and solutions for branded bag consumers via TikTok Shop. The research uses empirical juridical approach methods and the analysis uses qualitative descriptive. The type of data is primary data, namely observation and interviews. The results showed that barriers to legal protection for branded bag consumers on TikTok Shop include; dishonesty of business actors regarding the products they sell; discrepancy between the products ordered and those received by consumers; consumer incomprehension regarding the details of the products purchased, causing misunderstandings between consumers and business actors; and the return complaint process is not easy and takes a long time. The solution are that business actors are required to provide detailed information about the conditions and guarantees of goods and / or services; provide an explanation of the use, repair, and maintenance of the goods; business actors are responsible for providing compensation for damage, pollution, and/or loss of their consumers if there is a complaint; consumers must read and understand the details of the product to be purchased; and consumers follow the terms and conditions regarding the steps to return goods, such as; attach photo proof, receipt number, and unboxing video.